A white mulberry lesion in the retina (Indian Journal of Case Reports, 2020)
A routine fundus examination after dilated retinoscopy in a 9-year-old child revealed a white mulberry-like lesion with adjacent dilated vessels. After suspicion, systemic investigations were done for the child which included ultrasound abdomen and magnetic resonance imaging brain, both of which showed the presence of abnormal growths. We describe a case of a rare phakomatosis diagnosed primarily due to a unique ophthalmic lesion.